Open Educational Resources in Higher Education A Global Perspective - Olivier, Jako.; Rambow, Andreas (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book explores open educational resources and open education through research conducted on this topic globally. This book engages with intersections between open educational resources, social justice and equality, as well as policy in terms of open educational resources. Numerous examples of open praxis are also included, ranging from open educational resources courses to the affordances of artificial intelligence, data-driven learning, and open textbooks in this context. Furthermore, chapters range from providing a broad overview of open educational resources international and regional initiatives in Africa, to cases of work done in the United States, New Zealand, Israel, and Hong Kong. The role of Wikipedia and Wikidata is also prominent. Finally, this book includes unique contributions, focusing on open educational resources and feminist pedagogy, as well as disabled learners' motivations for participating in Massive Open Online Courses (MOOCs). Academics and researchers working in the field of open education and higher education in general will understand the importance of this work.
Chapter 1. OER: A catalyst for social justice and equality -- Chapter 2. OER: The promise, practice and problems -- Chapter 3. Developing supportive policies and strategies for their implementation: Student experience with real-world cases -- Chapter 4. Artificial intelligence-based techniques to assess and compare the quality of OER -- Chapter 5. Repositories of Open Textbooks for higher education: A worldwide overview -- Chapter 6. Reflections on remixing open access content into OER: A new paradigm for sustainable data-driven language learning systems design in higher education -- Chapter 7. OER: Guidelines in resource development for EAP -- Chapter 8. The collaborative picture book format as an OER for socialization, learning and assessment in higher education -- Chapter 9. Investigating disabled learners' motivations of participating in MOOCs: A mixed methods research -- Chapter 10. The Wikipedia Education Program as OEP: Global stories -- Chapter 11. Who builds it, who benefits? Deepening student and faculty knowledge about Wikipedia's scholarly value -- Chapter 12. OERs for data literacy and knowledge equity: Integrating Wikidata into higher education -- Chapter 13. Legacy building through a "Teaching with Technology" open textbook project -- Chapter 14. Integrating OER praxis and feminist pedagogy in Gender, Women's and Sexuality Studies.
Keywords: Educational technology; Education, Higher; Digital Education and Educational Technology; Higher Education